PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI PT EKADHARMA INTERNATIONAL TBK YOGYAKARTA - aditya hutama putra (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this research is to know (1) the influence of variable compensation against the motivation of working employees (2) the influence of work environment against the motivation of working employees and (3) the influence of environmental compensation and work environtment collectively against the motivation of working employees at PT. Ekadharma International Tbk. This research uses a type of quantitative research, the population in this study are all the employees of PT. Ekadharma International Tbk Yogyakarta which amounts to 50 employees. This research consist of variable compensation (K), work environment (LK), and work motivation (MK). This study uses saruration sampling. Data retrieval method using a questionnaire. Technical analysis used is multiple linear regression with 5% significant level. The result of this study obtained the regression equation MK = 0.261 + Compensation (K) 0.367+ (LK) work environment 0.684 with the calculation of t-test that the variable compensation (K) positively affect the motivation of work (MK) and it is significant. it can be seen from the significant value of variable compensation 0.001˂ 0.05. Work environment variable (LK) positively influence to work motivation (MK) and it is significant. It can be seen from the significant value 0.000 ˂ 0.05. From the results of F test obtained F count to 26,49 with significant level 0.000 ˂ 0.05 so it can be said that variable compensation and work environment influence to variable motivation of working employees.